Innovation in the Renewal of Islamic Religious Education Learning in the 21st Century Era - Firma, Heldi; Sri Muharyati; Zaitun (The Future of Education Journal, 2025)
Education in the 21st century has undergone significant changes due to technological advancements and social shifts. Innovation in Islamic Religious Education (IRE) learning is crucial to meet the needs of the millennial generation, which prioritizes knowledge and skills. The purpose of this study is to examine various innovations in IRE learning that can enhance the relevance and quality of education and educational content. This research uses a qualitative descriptive method through a literature study by analyzing relevant literature. The results show that the application of digital technology and student collaboration in the teaching and learning process can increase student participation and learning effectiveness, with a focus on learner-centered approaches. Therefore, there is hope for innovation among IRE graduates who are willing to face global challenges.